Zihaf and ʿIlal in Zuhayr ibn Abi Sulma’s Poem “’Afa min Ali Fatimata al-Jawa”: An Analytical Prosodic Study - Muhammad Suhil; Fahmi Sofyan; Aiyub Berdan (Pusaka Cendekia Indonesia Foundation, 2026)
This study identifies the poetic meter and maps the distribution of zihāf and ʿilal in Zuhayr ibn Abī Sulmā’s poem “ʿAfā min Āli Fāṭimata al-Jawāʾ.” It employs a qualitative-descriptive design with textual prosodic analysis. The corpus is the sixty-six-verse version adopted by the researcher. The procedure comprised text stabilization and vocalization, conversion into prosodic orthography, syllabic segmentation, matching with the feet of al-Wāfir, and coding and counting metrical alterations. The analysis indicates that all verses follow the complete al-Wāfir meter with clipped ʿarūḍ and ḍarb. Four types of zihāf occur in the internal feet: ʿaṣb in 62 positions, kaff in 7, ʿaql in 4, and naqṣ in 3. Qaṭf is present in every verse: 66 verses, equivalent to 132 metrical positions when the ʿarūḍ and ḍarb of each verse are counted separately. The study contributes a systematic quantitative and functional map of the metrical alterations across the entire poem and corrects its generic identification: the text is an independent poem, not Zuhayr’s famous Muʿallaqah beginning with “A-min Ummi Awfā.” The findings suggest that the high frequency of ʿaṣb and the regularity of qaṭf do not disrupt the meter; rather, they produce controlled rhythmic flexibility within the al-Wāfir system. Penelitian ini mengkaji bagaimana audiens digital membangun makna terhadap nasyid akapela Arab Kun Fayakun karya Othman Alibrahim melalui kerangka respons pembaca Wolfgang Iser. Penelitian menggunakan desain kualitatif interpretatif dengan menganalisis lima belas komentar publik YouTube yang didokumentasikan dari kolom komentar pertunjukan dan dipilih secara purposif karena secara langsung membahas penyanyi, pesan spiritual nasyid, atau respons afektif-simbolik. Identitas pengguna dianonimkan dan data dikodekan berdasarkan fokus respons, repertoar bersama, ketaktertentuan teks, dan konkretisasi audiens. Hasil penelitian menunjukkan tiga pola resepsi yang saling berkaitan. Pertama, respons estetis-performatif menonjolkan kejernihan vokal, penyajian akapela, dan ekspresivitas penyanyi. Kedua, respons spiritual-tekstual memaknai nasyid melalui repertoar Islam tentang kekuasaan Ilahi, doa, harapan, dan penyembuhan. Ketiga, respons simbolik-afektif menggunakan emoji serta ungkapan singkat untuk memadatkan kekaguman, kesedihan, ketenangan, dan kenyamanan spiritual. Penelitian ini menunjukkan bahwa komentar YouTube dapat memperlihatkan proses konkretisasi makna yang sering tidak terlihat dalam praktik pembacaan konvensional. Kajian ini memperluas penerapan teori Iser pada resepsi musik digital, sekaligus menegaskan bahwa korpus komentar purposif yang kecil tidak dapat mewakili seluruh audiens. تهدف هذه الدراسة إلى تحديد البحر الشعري، ورصد الزحافات والعلل، وبيان توزيعها في قصيدة “عفا من آل فاطمة الجواء” لزهير بن أبي سلمى. واعتمدت الدراسة المنهج الوصفي النوعي بالتحليل العروضي النصي، انطلاقًا من النسخة التي اتخذها الباحث أساسًا للتحليل، وتتكون من ستة وستين بيتًا. ومر التحليل بخمس مراحل: تثبيت النص وضبطه، وتحويله إلى الكتابة العروضية، وتقسيمه إلى مقاطع صوتية، ومطابقة المقاطع بتفعيلات بحر الوافر، ثم ترميز مواضع الزحاف والعلة وإحصاؤها. وأظهرت النتائج انتظام الأبيات جميعها في بحر الوافر التام ذي العروض والضرب المقطوفين. وسجل التحليل أربعة أنواع من الزحاف في الحشو: العصب في اثنين وستين موضعًا، والكف في سبعة مواضع، والعقل في أربعة مواضع، والنقص في ثلاثة مواضع. كما ثبت القطف في جميع الأبيات؛ أي في ستة وستين بيتًا، بما يعادل مئة واثنين وثلاثين موضعًا عروضيًا عند احتساب عروض كل بيت وضربه على حدة. وتتمثل جدة الدراسة في تقديم خريطة كمية ووظيفية للتغيرات العروضية في القصيدة كاملة، مع تصحيح توصيف النص بوصفه قصيدة مستقلة لا معلقة زهير المشهورة التي مطلعها «أمن أم أوفى». وتخلص الدراسة إلى أن كثافة العصب وثبات القطف لا يمثلان خروجًا على الوزن، بل يحققان مرونة إيقاعية منضبطة داخل نظام الوافر.